2021
DOI: 10.3390/joitmc7030176
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership and Employees’ Proactive Behaviour: Fortifying Self Determination Theory

Abstract: The prevailing pandemic (COVID-19) has increased socioeconomic problems and caused psychological distress due to work uncertainty, specifically in emerging economies. Small and medium enterprises (SMEs) in emerging economies have been severely affected. Particularly, work uncertainty is becoming a hindrance towards proactive work behaviour (PWB) that can be improved by an effective entrepreneurial leadership role and proactive personality attribute. Based on fortifying self-determination theory, this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 84 publications
2
20
0
2
Order By: Relevance
“…First, we suggest that SME hotels should understand the benefits of these leadership styles and recruit managers and supervisors who can lead entrepreneurially and ethically. In their recruitment and selection processes, hotels should search for particular personality traits, such as agreeableness and conscientiousness, which have been found to predict ethical leadership (Babalola et al , 2019; Garba et al , 2018) or characteristics, such as risk-taking and proactivity, which were identified as important characteristics of entrepreneurial leaders (Bilal et al , 2021). Hospitality organizations need to provide training on the benefits of these leadership styles and how to develop them.…”
Section: Discussionmentioning
confidence: 99%
“…First, we suggest that SME hotels should understand the benefits of these leadership styles and recruit managers and supervisors who can lead entrepreneurially and ethically. In their recruitment and selection processes, hotels should search for particular personality traits, such as agreeableness and conscientiousness, which have been found to predict ethical leadership (Babalola et al , 2019; Garba et al , 2018) or characteristics, such as risk-taking and proactivity, which were identified as important characteristics of entrepreneurial leaders (Bilal et al , 2021). Hospitality organizations need to provide training on the benefits of these leadership styles and how to develop them.…”
Section: Discussionmentioning
confidence: 99%
“…Employees’ proactive behaviors at work are vital for innovation in organizations [ 1 ]. Previous studies have shown that leadership plays an important role in facilitating employees’ proactive behaviors [ 2 , 3 , 4 ]. More recently, a growing body of research has emphasized the role of leaders’ humor at work as an important way of cultivating followers’ innovative and creative thinking [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, future studies should investigate the impact of entrepreneurial leadership on proactive employee behavior from a dynamic development perspective. Second, to reduce common method bias, we used a predictive time lag research design as executed by previous researchers (e.g., Neubert et al, 2008 ; Demirtas, 2015 ; Kim and Beehr, 2017 ; Zohar and Polachek, 2017 ; Bilal et al, 2021 ). The robust causal implication could not be drawn based on the time lag study.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, self-determination theory is adequate and efficient in aligning societal shift to individual autonomy, demonstrating a fact-base process of involvement and motivation with robustness to suspend conventional transaction reasoning about workplace motivation. Furthermore, self-determination theory has revealed how its motivational “act” envisage vital organizational up shots like wellbeing (Gagné and Deci, 2005 ; Vansteenkiste et al, 2007 ), proactive work behavior (Bilal et al, 2021 ) commitment (Olafsen et al, 2017 ; Becker et al, 2018 ), innovative work behavior (Wang et al, 2021 ), talent retention (Fowler, 2014 ; Bock, 2015 ), and financial performance (Deci et al, 2017 ), among other necessary performance measures. Finally, SDT narrates a comprehensive model for assessment and suggests a well-defined framework for taking the initiative to enhance and maintain involvement and motivation (e.g., Deci et al, 1989 ; Hardré and Reeve, 2009 ).…”
Section: Introductionmentioning
confidence: 99%